Julie Coleman and Christian J. Kay (Eds.). Lexicology, Semantics and Lexicography: Selected Papers from the Fourth G.L. Brook Symposium, Manchester, August 1998. - Carstens, Adelia; van Huyssteen, Gerhard B. (Lexikos, 2002)
NVolume 194 of the series Current Issues in Linguistic Theory, entitled Lexicology, Semantics and Lexicography, comprises a selection of eleven academic contributions that were originally presented at the Tenth International Conference of English Historical Linguistics. The disciplinary focus of this volume of texts is the diachronics of English vocabulary, and the representation thereof in dictionaries. From a theoretical point of view prototype theory assumes a central position, and the methodological approach is mainly corpus-analytical.